Weather, the Forgotten Factor in Business Cycle Analyses - Roland Döhrn; Philipp an de Meulen (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
In periods of unusual weather, forecasters face a problem of interpreting economic data: Which part goes back to the underlying economic trend and which part arises from a special weather effect? In this paper, we discuss ways to disentangle weather-related from business cycle-related influences on economic indicators. We find a significant influence of weather variables at least on a number of monthly indicators. Controlling for weather effects within these indicators should thus create opportunities to increase the accuracy of indicator-based forecasts. Focusing on quarterly GDP growth in Germany, we find that the accuracy of the RWI short term forecasting model improves but advances are small and not significant.
Keywords: C53; E37; 330; weather; short term forecasting; bridge equations; forecast accuracy